Will the Amaranthus tuberculatus Resistance Mechanism to PPO-Inhibiting Herbicides Evolve in Other Amaranthus Species?. (15th March 2012) - Riggins, Chance W.; Tranel, Patrick J.
Abstract : Resistance to herbicides that inhibit protoporphyrinogen oxidase (PPO) has been slow to evolve and, to date, is confirmed for only four weed species. Two of these species are members of the genus Amaranthus L. Previous research has demonstrated that PPO-inhibitor resistance in A. tuberculatus (Moq.) Sauer, the first weed to have evolved this type of resistance, involves a unique codon deletion in the PPX2 gene. Our hypothesis is that A. tuberculatus may have been predisposed to evolving this resistance mechanism due to the presence of a repetitive motif at the mutation site and that lack of this motif in other amaranth species is why PPO-inhibitor resistance has not become more common despite strong herbicide selection pressure. Here we investigate inter- and intraspecific variability of the PPX2 gene—specifically exon 9, which includes the mutation site—in ten amaranth species via sequencing and a PCR-RFLP assay. Few polymorphisms were observed in this region of the gene, and intraspecific variation was observed only in A. quitensis . However, sequencing revealed two distinct repeat patterns encompassing the mutation site. Most notably, A. palmeri S. Watson possesses the same repetitive motif found in A. tuberculatus . We thus predict that A. palmeri will evolve resistance to PPO inhibitors via the same PPX2 codon deletion that evolved in A. tuberculatus .